Pengaruh Self Efficacy dan Individual Inovation Capability Terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Mediasi di Balai Wilayah Sungai Maluku - Tama Raya Silitonga; Fransiska Natalia Rahallo; Conchita Valentina Latupapua (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the influence of self-efficacy and individual innovation capability on employee performance, with work motivation as a mediating variable at the Maluku River Basin Office. A quantitative approach was used in this study, with data collection methods through the distribution of online questionnaires to 93 Maluku River Basin Office employees. The data obtained were then analyzed using a path analysis model and SEM-PLS analysis tools to test the direct and indirect relationships between variables. The results showed that self-efficacy and individual innovation capability have a positive and significant influence on employee work motivation. These two variables also have a positive and significant influence on employee performance. In this case, the self-efficacy variable is proven to have a significant influence on employee performance, indicating that employees' self-confidence in their ability to achieve goals can improve their performance results. Similarly, individual innovation capability has a significant influence on employee performance, indicating that employees' ability to innovate individually also plays a role in increasing productivity and work results. In addition, this study also found that work motivation has a significant influence on employee performance, confirming the importance of motivation in achieving optimal performance. Work motivation has also been shown to function as a mediator, able to mediate the influence of self-efficacy and individual innovation capability on employee performance. In other words, increasing individual self-efficacy and innovation capability can strengthen work motivation, which in turn will improve employee performance. This research provides useful insights for developing managerial strategies, particularly in human resource management to improve employee performance in government institutions such as the Maluku BWS.